Revisiting the Relationship between Energy Price Fluctuations, Forestry, Environmental Governance, and Energy Transition on Carbon Emissions: Evidence from Indonesia - Sosilawaty Sosilawaty; Johanna Maria Rotinsulu; Wahyudi Wahyudi; Yessiarie Silvanny Sibot; Nyahu Rumbang (International Journal of Energy Economics and Policy, 2023)
This paper summarizes the role of energy price fluctuation, forestry, environmental governance, and energy transition on carbon emissions. Since, industrialization and population growth, both are the factors which according to literature are culprits of environmental pollution or sometimes benefits the environment, hence, the contradictory statement of scholars urges the authors to introduce these two variables as a control variable in proposed framework. To analyze the time series data in the time span of 1986-2019, the study used DARDL approach and from the results it has been revealed that energy price fluctuation, forestry, environmental governance, environmental governance, energy transition and population growth increases environmental protection by reducing harmful emission. Based on the results, an empirical baseline is provided to policy makers to strategize their agenda and promote the usage of renewable resources.